A personalized integrative approach to recurrent glioblastoma: Exploring the role of cannabinoids and hyperbaric oxygen in a real-world case (Indian Journal of Case Reports, 2025)
Glioblastoma multiforme (GBM) is the most aggressive form of primary brain tumor in adults, associated with poor prognosis and high recurrence rates despite multimodal standard therapies. Cannabinoid therapy has recently emerged as a potential adjuvant due to its anti-tumor properties. We present a 68-year-old male with recurrent right temporal lobe GBM (World Health Organization Grade 4), previously managed with craniotomy and radiotherapy. Following recurrence, a personalized integrative approach using temozolomide, oral cannabinoids (tetrahydrocannabinol/cannabidiol), and hyperbaric oxygen therapy (HBOT) was initiated at our center. The patient showed a 38.25% reduction in tumor volume, significant clinical improvement, and resolution of symptoms without adverse effects. The integrative use of temozolomide, cannabinoids, and HBOT appears promising in recurrent GBM management. The case highlights the need for further exploration of cannabinoid-based and adjunctive therapies in glioblastoma treatment.